Integration of Absolute Authority of District Courts and State Administrative Courts in Land Disputes through Koneksitas Courts - Yuherman Yuherman; Wahyu Nugroho; Eko Nuriyatman; Hartinie Abd Aziz (Fakultas Hukum Universitas Lampung, 2025)
Land disputes in Indonesia often encounter legal uncertainty due to the rigid separation of judicial authority between district courts, which adjudicate ownership disputes, and state administrative courts (PTUN), which review the legality of land ownership certificates. This jurisdictional divide frequently leads to inconsistent or contradictory rulings over the same land, reflecting a systemic challenge in the Indonesian judicial system. This research examines mechanisms to overcome the impasse of absolute competence between the two courts, focusing on the development of a connectivity court model that integrates their functions. Employing a normative legal method with a statutory approach, the study proposes the modification of procedural law to establish a connectivity court that enables joint adjudication of civil ownership and administrative certificate disputes. Such a mechanism not only ensures legal certainty and coherence in decisions but also promotes justice that is simple, efficient, and affordable, while optimizing existing judicial infrastructure and avoiding the complexities and costs associated with creating a specialized agrarian court.